Pattula’ Bala as a Discursive Tradition: The Reception of the Qur’an in the Muslim Bugis Community - Amir, Abdul Muiz (Balai Penelitian dan Pengembangan Agama Makassar, 2022)
This article examines the Pattula' Bala (PB) practice by the Bugis Muslim community in Indonesia, especially in Kendari City. PB is the practice of displaying the verses of the Qur’an, which its users in certain places install intending to prevent them from calamity. This article aims to reveal the genealogy of the PB tradition as part of the discursive Islamic tradition. This study uses a descriptive-analytic design from interview data, documentation, and literature exploration. The data were analyzed using the genealogical theory developed by Talal Asad and the exegetical reception approach developed by Ahmad Rafiq, especially in Qur’anic studies discourse. Research findings show that the Bugis Muslim community practices PB as a repellent to disasters and as a motivation to be more active in worship (tabarruk). Historically, information about similar practices is also found in Hadith and Faḍā’il ‘Amal literature. However, they have undergone a process of transmission and transformation from time to time until the entry of Islam into Sulawesi. This process cannot be separated from the role of religious figures who introduced Islam in Sulawesi through a Sufistic or mystic approach. Nevertheless, these findings still require philological studies, so the claims of this study are more convincing historically. The implication of this research is to synthesize the claim of “Islam as a discursive tradition,” which is claimed by Talal Asad. Keywords: Discursive Tradition, Pattula’ Bala’, the Muslim Bugis Community, Qur’anic Reception. Artikel ini mengkaji tentang praktik Pattula’ Bala (PB) oleh komunitas Muslim Bugis di Kota Kendari. PB merupakan praktik pajangan ayat-ayat Al-Qur’an yang dipasang oleh penggunanya di tempat-tempat tertentu dengan tujuan agar mereka terhindar dari musibah. Artikel ini bertujuan untuk mengungkap genealogi tradisi PB sebagai bagian dari tradisi Islam yang bersifat diskursif. Penelitian ini menggunakan desain deskriptif analitik dari data wawancara, dokumentasi, dan eksplorasi literatur. Teknik wawancara dan dokumentasi digunakan untuk memeroleh data terkait bentuk praktik PB oleh komunitas Muslim Bugis. Data dianalisis menggunakan teori genealogi yang dikembangkan oleh Talal Asad yang dikombinasikan dengan pendekatan exegetical reception yang dikembangkan oleh Ahmad Rafiq, khususnya dalam wacana studi Al-Qur’an. Temuan penelitian menunjukkan bahwa komunitas Muslim Bugis mempraktikkan PB tidak hanya Pattula’ Bala as a Discursive Tradition: The Reception of the Qur’an.... – Abdul Muiz Amir 2 sebagai penolak bencana, melainkan juga sebagai motivasi untuk lebih giat dalam beribadah (tabarruk). Secara historis, informasi tentang praktik yang serupa juga ditemukan dalam literatur Hadis dan Faḍā’il ‘Amal, meskipun telah mengalami proses transmisi dan transformasi dari masa ke masa hingga masuknya Islam di Sulawesi. Proses tersebut tidak terlepas dari peran tokoh agamawan yang memperkenalkan Islam di Sulawesi melalui pendekatan sufistik atau mistisisme. Meskipun demikian, temuan ini masih membutuhkan studi filologi, sehingga klaim penelitian ini lebih meyakinkan secara historis. Implikasi penelitian ini berperan sebagai sintesis terhadap klaim “Islam as a discursive tradition” oleh Talal Asad.